(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Lestari ND, Suprayogo D, Rachmansyah A. 2018. Local biodiversity conservation in Sigi, Central Sulawesi, Indonesia: Analysis of the effect of elevation, land accessibility, and farmers’ income and perception on vegetation diversity in agroforestry systems. Biodiversitas 19: 283-291. The objectives of the research were to evaluate the level of landscape vegetation diversity in agroforestry systems and to determine the effect of elevation, accessibility, and farmer’s income and perception on vegetation diversity in agroforestry systems. The research was conducted in Sigi District, Central Sulawesi, Indonesia. The method used was the Multidisciplinary Landscape Assessment approach. The research sites were located in 3 districts and 6 representative villages i.e. Padende and Sibedi in the lower landscape (23-75 m asl.), Balane and Doda in the middle landscape (148-504 m asl.), Dombu and Ongulero in the upper landscape (1163-1404 m asl.), with 5 replications in each village. The total area of the six villages was 3772.13 ha that consisted of 1217.13 ha of agroforestry systems (32.3%). The research covered a population of 392 households who had landed with agroforestry systems. A total of 30 agroforestry farmers and their land (minimum 0.25 ha, homogeneous land system) were selected as samples. Research activities like observation, survey, and analysis were divided into two aspects, namely biophysical and socioeconomic aspects. The results revealed that at landscape level agroforestry systems had relatively high plant species diversity (H’= 3.1) and needed to be optimized to enhance its role as buffering zone for biodiversity conservation and for supporting sustainable livelihood. Efforts to improve vegetation diversity must be adjusted to habitat conditions (elevation and soil health), where vegetation can grow and produce well. The regional development such as accessibility improvement is still needed and it will not threaten the vegetation diversity as long as there is a harmony between human activities and the environment. An increase in the level of income with a positive perception of farmers on the benefits of vegetation diversity in the future will have a main role in vegetation diversity conservation as fundamental asset in sustainable development.